Marcos Ancelovici, Pascale Dufour and Héloïse Nez (eds., 2016), Street Politics in the Age of Austerity: From the Indignados to Occupy, Amsterdam: Amsterdam University Press, 2016. - Raffaele Bazurli (Coordinamento SIBA, 2019)
For Book Reviews Abstract is not required